Cariprazine as a treatment for negative psychotic symptoms in first-episode psychosis: case series. Issue 3 (28th May 2022) - Demjaha, Arsime; Iacoponi, Eduardo; Hansen, Lars; Peddu, Pradeep; McGuire, Philip
Abstract : Negative psychotic symptoms are among the most disabling features of schizophrenia, and are strongly associated with relatively poor clinical and functional outcomes. However, there are no effective treatments for negative symptoms, and this represents a major unmet clinical need. Recent research has shown that negative symptoms are already present in many patients at illness onset. There is evidence that cariprazine may improve negative symptoms in patients with chronic schizophrenia. However, its utility in treating negative symptoms in the early stage of the disorder is unclear. Here, we report six cases of patients with first-episode psychosis who were treated with cariprazine.